Hints on the Late Miocene Evolution of the Tonale-Adamello-Brenta Region (Alps, Italy) Based on Allochtonous Sediments From Raponzolo Cave - Sauro, Francesco; Fellin, Maria Giuditta; Columbu, Andrea; Häuselmann, Philipp; Borsato, Andrea; Carbone, Cristina; De Waele, Jo (Frontiers in Earth Science, 2021)
Raponzolo is a paleo-phreatic cave explored in 2011 in the Brenta Dolomites (Trentino, Italy), at the remarkable altitude of 2560 m a.s.l.. Differently to all other nearby Alpine caves, it hosts well-cemented fine- to medium sands of granitic-metamorphic composition. The mineralogy suggests a sediment source from the Adamello and Tonale Unit, separated from the Brenta by one of the most important tectonic lineaments of the Alps (Giudicarie Line). The fine sand was sampled to determine burial time and thus a minimum age of the cave. Cosmogenic isotopes (26Al and 10Be) in quartz grains allowed to estimate a minimum burial age of 5.25 Ma based on the mean surface sediment transport time, and to infer the original altitude of the catchment area. Detrital apatite fission-track (AFT) and U-Pb zircon dating provide information on the source, both from a regional and altitude (exhumation) perspective. Two populations of detrital AFT ages center at 17 (-2.3 +2.6) and 23 (-3.3 +3.9) Ma, whereas the main detrital zircon U-Pb age populations are younger than 40 Ma. These correspond to intrusive and metamorphic sources nowadays outcropping exclusively above 2200-2300 m a.s.l. in Northern Adamello and Tonale. The results point to a Late Miocene erosion and cave infilling by allochthonous sediments, with important implications on the timing of speleogenesis, as well as the paleogeographical connection, tectonic evolution and uplift of different structural units of the Alps. The roundness and the well sorted size of the quartz grains suggest a fluvial or aeolian origin, possibly recycled by glacial activity related to cold events reported in several high latitude areas of the world at 5.75 and 5.51 Ma. These glacial phases have never been documented before in the Alps. This information confirms that the valleys dividing these geological units were not yet deeply entrenched during the onset of the Messinian Salinity Crisis (5.6-5.5 Ma), allowing an efficient transport of sediments across major Alpine tectonic lineaments. This study shows the potential of cave sediments to provide information not only on the age of speleogenesis but also on the paleogeography of a wide area of the Alps during the Late Miocene.